Development of a measure to assess vaccine confidence among men who have sex with men - Paula M. Frew; Ian W. Holloway; Cameron Goldbeck; Diane Tan; Elizabeth Wu; Juan Jauregui; Vincent L. Fenimore; Laura A. Randall; Chelsea S. Lutz; Judith Mendel; Ann L. Aikin; Glen J. Nowak; et al. (Taylor & Francis Group, 2018)
Background: Recent serogroup C meningococcal disease outbreaks led to meningococcal vaccine recommendations for Southern California men who have sex with men (MSM). Assessment of vaccine confidence is critical to improving vaccine coverage in the context of disease outbreaks wherein immunization(s) are recommended. Methods: We surveyed MSM using venue-based sampling and began development of the vaccine confidence index (VCI) with 30 survey items corresponding to trust- and safety-related perceptions. We performed exploratory factor analyses and computed the Cronbach's alpha coefficient to assess internal consistency of the VCI. We created a categorical confidence variable (low, medium, and high confidence) and conducted bivariate and multivariate analyses to evaluate associations with reported confidence and immunization uptake. Results: Ten survey items were included in the final VCI and formed the confidence measure. Participants with low confidence had the lowest levels of reported uptake for both meningococcal vaccines. Confidence differed significantly (p ≤ 0.05) between MSM who indicated they received vaccines recommended within the context of the outbreak and those who did not. Conclusions: Our VCI is sensitive to a number of issues that may influence vaccine confidence. It is useful for assessing MSM trust and acceptance of recommended immunizations and may be used to inform intervention development.